Exploring the Use of Co2-Expanded Ionic Liquids as Solvents in Microextraction of 3,3′,4,4′-Tetrachlorobiphenyl from Aqueous Solutions - Sepulveda-Cuevas, L; Romero-Figueroa, J; Toledo-Neira, C; Toledo-Neira, C; Quijada-Maldonado, E (Elsevier B.V., 2024)
This paper explores the effect of adding supercritical carbon dioxide (scCO2) to Ionic Liquids (ILs) for the microextraction of very diluted pollutants from aqueous matrices. The proposed system uses an IL, trihexyl-tetradecyl-phosphonium bis(trifluoromethylsulfonyl)imide ([P6,6,6,14][Tf2N]) and 1-hexyl-3-methyl-imidazolium tris(pentafluoroethyl)trifluorophosphate ([hmim][FAP]), as extractant, and scCO2 as diluent that may change the solvent capacity by changing the solvent polarity. The study was first carried out for the extraction of 3,3′,4,4′-tetrachlorobiphenyl (PCB-77) from aqueous solutions using a designed microextraction cell. Different ILs, sample volumes and kinetics of extraction were investigated. Results show that within 15 min the maximum extraction percentage was achieved employing a scCO2 partial pressure of 80 bar. To investigate the influence of the polarity change by the presence of carbon dioxide more broadly, other pollutants with different water solubilities were used. It was observed that scCO2 (partial pressure) reduced the recoveries for benzophenone and PCB-77 but increased the extraction of triclosan. This is due to the change on solvent s polarity and viscosity of the mixture. This was corroborated through a ternary system simulation including IL-pollutant-scCO2. All these results establish that the combination of CO2 and IL can in some cases enhance the extraction, but the affinity between the pollutant and scCO2 is a key parameter that discerns whether expanding the IL with scCO2 is beneficial for the extraction. © 2023